Transformasi Media Sosial dalam Praktik Public Relations: Tinjauan Literatur - Ahmad Zakki Abdullah; Mia Nurmiarani; Priyono Sadjijo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The development of social media has transformed the landscape of communication and Public Relations (PR) practices. In this digital era, PR practitioners are required to understand and utilize social media effectively in efforts to build strong relationships with the public. This study aims to investigate the role of social media in PR practices, focusing on identifying current trends, changes, and challenges faced by PR practitioners in adopting social media. The method of literature review is used to gather and analyze information from various sources. The research findings show that social media has become an integral component in PR strategies, enabling practitioners to interact directly with the public, respond to issues in real-time, and measure their communication impact more accurately. Recent trends highlight the importance of visual content, collaboration with influencers, and attention to sustainability and social responsibility issues. In conclusion, the transformation of social media has had a significant impact on PR practices, expanding reach, increasing engagement, and allowing for more accurate performance measurement.